Enhanced deep-ultraviolet sensing by an all-inorganic p-PZT/n-Ga2O3 thin-film heterojunction. (24th February 2021) - Liu, Zeng; Zhang, Shaohui; Zhi, Yusong; Li, Shan; Yan, Zuyong; Chu, Xulong; Bian, Ang; Li, Peigang; Tang, Weihua
Abstract: In this work, an enhanced-performance deep-ultraviolet (DUV) photodetector based on a Ga2 O3 /lead zirconate titanate (Pb(Zr0.52 Ti0.48 )O3, PZT) p-n heterojunction is fabricated and characterized for the first time. Compared to a Ga2 O3 -based device, the heterojunction device achieved a lower dark current of 2.7 × 10 −11 A, a higher photo- to dark-current ratio of 2 × 10 3, a higher responsivity of 5.5 mA W −1, a larger specific detectivity of 2.6 × 10 11 Jones and a higher external quantum efficiency of 2.7% at −2 V under 254 nm UV light illumination with an intensity of 500 μ W cm −2 . The p-PZT/n-Ga2 O3 was confirmed to be a potential candidate for the construction of DUV photodetectors with enhanced sensing performance.